1‐Thia‐4, 7‐diaza‐spiro[4.4]nonane‐3, 6‐dione: A Structural Motif for 5‐hydroxytryptamine 6 Receptor Antagonism. (26th December 2013) - Hostetler, Greg; Dunn, Derek; McKenna, Beth A.; Kopec, Karla; Chatterjee, Sankar
<x xml:space="preserve">Abstract</x> A series of potent 5‐hydroxytryptamine 6 (5‐HT6) receptor antagonists based on 1‐thia‐4, 7‐diaza‐spiro[4.4]nonane‐3, 6‐dione motif has been disclosed. Enantiomers of potent racemate compound 8a (Ki = 26 nm) displayed difference in activity (Ki of 15 nm versus 855 nm) signaling the influence of the stereochemistry of the chiral center on potency. In addition, the potent enantiomer displayed significant selectivity in biological activities over several related family members.